Chemical Control of the Invasive Tree Ailanthus altissima - Jordi Soler; Jordi Izquierdo (Agriculture)
Many natural areas are colonised by the invasive species Ailanthus altissima (Mill.) Swingle. Its presence in natural ecosystems damages the ecological richness while competing with native flora. A. altissima is one of the most widespread weed species in natural areas of temperate regions such as conservation parks, archaeological sites and communication corridors. Not many active ingredients are available to control this weed since the most popular, glyphosate, has been banned by many municipalities. To test the efficacy of alternative herbicides, naturally occurring populations in Collserola Conservation Park in Barcelona (Catalonia, Spain) were treated with different herbicides using three different techniques. Aclonifen, metribuzin, flazasulfuron, metsulfuron-methyl, fluroxypyr, isoxaflutole + thiencarbazone-methyl and triclopyr mixed with 2.4-D, fluroxypyr, aminopyralid and clopyralid were applied by stem injection, cut stump injection or basal bark techniques to trees of about 5 cm diameter. Cut stump and stem injection both gave almost total control of the trees while basal bark showed more varied results depending on the herbicide. The best control was achieved when flazasulfuron or triclopyr were present as active ingredients and poorer control was observed when using metsulfuron-methyl or isoxaflutole + thiencarbazone-methyl. Aclonifen showed no damage to the trees. Metribuzin worked better if the cut stump injection technique was used. These results showed that several alternatives are available to the use of glyphosate, which has been banned for some uses due to environmental concerns.